The Effect of Self-Management Training Using CD on the Quality of Life in Patients with Chronic Heart Failure - Tahereh Najafi Ghezeljeh; Alireza Abbasi; Mansoureh Oshgholi Farahani; Nasim Naderi (Iran University of Medical Sciences, 2016)
Background: Chronic heart failure (CHF) can have negative effects on the quality of life (QoL). Self-management education is one of the approaches that can be adopted to increase the QoL of these patients. This study aimed to determine the effect of self-management training using compact disc (CD) on the QoL in patients with CHF. Methods: This study was a non-randomized controlled clinical trial which was conducted on 74 patients with CHF hospitalized in Shahid Rajaie Cardiovascular medical and research center in 2015. Research samples were selected with convenience sampling method and randomly assigned to intervention (training with CD) and control (conventional training) groups. To collect data, Iranian questionnaire to assess QoL in patients with heart failure (IHF-QoL) was completed in both groups before and 3 months after the intervention. Data analysis was done using statistical tests of the Independent t test and paired t-test using SPSS version 21. Results: According to the findings, there was no significant difference between two groups before the intervention with regard to QoL scores (P=0.58). Statistical tests showed that 3 months after the intervention, self-management education promoted QoL subscales including psychological status (t=-2.578, P=0.012), self-care (t=-3.633, P=0.001), as well as total QoL (t=-2.01, P=0.048) in patients in the intervention group as compared with the control group. Also in CD method group, themean scores of total QOL and its subscales before the intervention were significantly different from that mean scores 3 months after the intervention., i.e. their total QOL and its all subscales improved after intervention. (P<0.0001). Conclusion: As self-management training with CD can improve QoL in patients with CHF compared with conventional training method, it is suggested that this training method be considered as a part of patients' self-management education by nurses with the aim of improving QoL.